TEORI BEBAN KOGNITIF JOHN SWELLER DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA ARAB PADA JENJANG PENDIDIKAN DASAR - Syagif, Ahmad (Prodi PGMI STIT Sunan Giri Bima, 2024)
This study aims to explain the concept of Cognitive Load Theory developed by John Sweller and its implications for Arabic language learning at the elementary education level. Using a literature review approach and descriptive-analytical techniques, this study provides an in-depth analysis of relevant literature. The findings reveal that Cognitive Load Theory highlights the limitations of working memory in processing information, which includes intrinsic, extrinsic, and germane cognitive loads. In Arabic language learning, this theory guides educators to reduce intrinsic cognitive load through simplifying teaching materials and introducing concepts gradually. Additionally, extrinsic cognitive load can be minimized by improving the quality of media, teaching materials, and relevant interactive teaching strategies. Meanwhile, germane cognitive load can be optimized through learning activities that reinforce students' cognitive schemas, such as contextual practice, visualization, and consistent repetition. Implementing this theory makes learning more effective and efficient, helping students gradually overcome the complexities of the Arabic language. Consequently, students' learning motivation is maintained, and the learning process becomes more meaningful. These findings are relevant for developing learning strategies oriented toward the cognitive needs of students at the elementary education level.